(untitled) (Colombia Medica, 1989)
Acute fatty liver of pregnancy is a rare disease that is difficult to diagnose and treat. The maternal and child prognosis is related to an early diagnosis. When this is not made, the course followed is toward a severe hepatic failure. There are very few reported cases in Colombia, three of which were previously described in 1970 in this hospital. Three patients studied at the Hospital Universitario del Valle in Cali, Colombia, between January 1985 and December 1988 are presented. These patients’ clinical and pathological characteristics are very similar to those found in other cases. Early diagnosis and termination of pregnancy are the therapeutic measures accepted in recent reports in the literature.